2018
DOI: 10.1016/j.newideapsych.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Components of cultural complexity relating to emotions: A conceptual framework

Abstract: Many cultural variations in emotions have been documented in previous research, but a general theoretical framework involving cultural sources of these variations is still missing. The main goal of the present study was to determine what components of cultural complexity interact with the emotional experience and behavior of individuals. The proposed framework conceptually distinguishes five main components of cultural complexity relating to emotions: 1) emotion language, 2) conceptual knowledge about emotions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…As Eid and Diener (2001) pointed out, a Chinese sample consistently showed the lowest experiences in almost all emotions, because Chinese culture considers emotions as dangerous, irrelevant or even illness-causing. Regulation strategies, such as the suppression of emotions, are generally suggested to be highly valued in East Asian cultures, and the value of a moderated emotional life can also be found in these cultures (Trnka, Šolcová, & Tavel, 2018). Future research on cross-cultural differences in emotion-related values should provide us with further insights into various levels of EC in different countries and cultures.…”
Section: Discussionmentioning
confidence: 96%
“…As Eid and Diener (2001) pointed out, a Chinese sample consistently showed the lowest experiences in almost all emotions, because Chinese culture considers emotions as dangerous, irrelevant or even illness-causing. Regulation strategies, such as the suppression of emotions, are generally suggested to be highly valued in East Asian cultures, and the value of a moderated emotional life can also be found in these cultures (Trnka, Šolcová, & Tavel, 2018). Future research on cross-cultural differences in emotion-related values should provide us with further insights into various levels of EC in different countries and cultures.…”
Section: Discussionmentioning
confidence: 96%
“…Lidské emoce jsou tedy nutně propojeny s jazykem, ve kterém komunikujeme, i s kulturou, ve které žijeme a se kterou interagujeme (např. Trnka et al 2018). Proto se nám zdá legitimní řešit otázku, co zahrnuje lužickosrbský "HNĚW", pouze z hlediska lingvistiky.…”
Section: Valence Emočních Predikátů -Sémantika a Syntaxunclassified
“…Thus, the way worry is felt and expressed is not only biologically determined but also influenced by cultural context [ 12 ]. Cross-cultural studies have shown that emotions and their expression, valence, and regulation vary among countries with different cultural values [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%